Reasons for non-vaccination and incomplete vaccinations among children in Pakistan. Issue 35 (23rd August 2018) - Riaz, Atif; Husain, Sara; Yousafzai, Mohammad Tahir; Nisar, Imran; Shaheen, Fariha; Mahesar, Waheed; Dal, Saleh Muhammad; Omer, Saad B.; Zaidi, Shehla; Ali, Asad
Abstract: Background: Global immunization efforts have received a boost through the introduction of several new vaccines. These efforts however, are threatened by sub-optimal vaccine coverage, particularly in countries with large birth cohorts. Pakistan has one of the largest birth cohorts in the world, where coverage of routine vaccination remains persistently inadequate. We undertook this study to ascertain reasons for non-vaccination or incomplete vaccination of children less than two years in 8 districts of southern Pakistan. Methods: A cross-sectional survey using WHO recommended rapid coverage assessment technique was conducted in 2014. Using probability proportional to size method, we sampled 8400 households with eligible children (aged 4–12 months). Using a structured questionnaire, mothers or other primary caregivers were interviewed to determine vaccination status of an index child. In case of non-vaccination or incomplete vaccination, respondents were asked for reasons leading to low/no vaccine uptake. Results: Based on both vaccination record and recall, only 30.8% of children were fully vaccinated, 46% had an incomplete vaccination status while 23%were non-vaccinated. The most frequently reported reasons for non-vaccination included: mothers/caregivers being unaware of the need for vaccination (35.3%), a fear of side effects (23%), mother/caregiver being too busy (16.6%), distance from vaccination centers (13.8%), and non-availability of either vaccinators or vaccines at vaccination centers (10.7%). Reasons identified for incomplete vaccination were similar, with caregivers being unaware of the need for subsequent doses (27.3%), non-availability of vaccinators or vaccines (17.7%), mother/caregiver being too busy (14.8%), fear of side effects (11.2%), and postponement for another time (8.7%). Conclusion: Various factors result in non-compliance with vaccination schedules and vaccine refusal within the surveyed communities, ranging from lack of knowledge to non-availability of supplies at vaccination centers. These barriers are best addressed through multi-pronged strategies addressing supply gaps, increasing community awareness and enhancing demand for routine vaccination services.